Politeness Strategies in Social Media (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines the use of politeness strategies in social media interactions, focusing on user comments addressed to public figures. As social media increasingly functions as a public communication space, language use within it reflects not only personal expression but also social norms, power relations, and considerations of face. Despite the informal and anonymous nature of online platforms, users often display strategic language choices to manage interpersonal relationships and avoid face-threatening acts. This research aims to identify the types of politeness strategies employed by social media users, determine the most dominant strategy, and explain the reasons underlying its use. The study adopts a qualitative descriptive approach. The data consist of 100 purposively selected comments collected from Instagram, Facebook, and YouTube, taken from posts by three highly visible public figures: a head of state, a global music celebrity, and a technology entrepreneur. Data analysis is guided by Brown and Levinson’s politeness theory, which categorizes strategies into positive politeness, negative politeness, bald on record, and off record. The findings indicate that positive politeness is the most frequently used strategy (78%), followed by negative politeness (11%), bald on record (10%), and off record (1%). The dominance of positive politeness suggests that social media users tend to maintain friendliness, show approval, and express respect, particularly when interacting with figures of authority or high public status. These findings demonstrate that digital communication continues to mirror offline social norms and highlight the continued relevance of politeness theory in online discourse.